Solve `-3t-8+7t = 34+9t-2`

First combine like terms on each side of the equal sign.

`4t - 8 = 9t + 32`

Next, move constants together and/or move variables together.

Subtract 4t from each side.

`4t-4t-8 = 9t-4t + 32`

`0-8=5t+32`

`-8 = 5t + 32`

Subtract 32 from each...

## See

This Answer NowStart your **48-hour free trial** to unlock this answer and thousands more. Enjoy eNotes ad-free and cancel anytime.

Already a member? Log in here.

Solve `-3t-8+7t = 34+9t-2`

First combine like terms on each side of the equal sign.

`4t - 8 = 9t + 32`

Next, move constants together and/or move variables together.

Subtract 4t from each side.

`4t-4t-8 = 9t-4t + 32`

`0-8=5t+32`

`-8 = 5t + 32`

Subtract 32 from each side.

`-8-32 = 5t+32-32`

`-40 = 5t+0`

`-40=5t`

Now divide both sides by 5.

`(-40)/5 = (5t)/5`

`-8 = t`

**The solution is t = -8.**